“Making the Art of Fun Freely Accessible”: Community Arts Practices and the Politics of Leisure in Britain in the 1970s and 1980s - Mathilde Bertrand (Angles, 2017)
The concept of leisure offers an interesting prism for the analysis of the community arts movement in Britain. The emergence of community arts from the late 1960s was closely related to a critique of the exclusive character of mainstream art appreciation and practice and to the struggle for people's access to the means of cultural production. As a tool, leisure was used by practioners to enable the expression of usually unheard voices, thus fostering processes of “authorisation”. Instead of being considered as a secondary claim, access to leisure, with its rich associations with play, “fun” and recreation, was given pride of place in the movement's practical and political framework. It became a political aim: that of opening alternative spaces and of harnessing the dynamic and subversive dimension of creative expression in the encouragement of collective action at a local level. In a crucial way, community arts projects asserted the equal validity of all cultural forms and signifying practices, therefore challenging classical definitions of art. The cultural pluralism advocated by community artists confronted the distinction between “high” and “low” culture and sought instead to redefine art around the concept of expression, away from the figure of the individual artist and towards the possibility of co-authorship in the production of collective meanings. The article analyses the politics of leisure produced by community arts organisations both in discourse and practice. Based on archival sources from several organisations as well as interviews with former members, the study offers a survey of different practices and identifies core principles of the movement: accessibility, collective action, empowerment, and cultural democracy. These themes were jeopardized in the 1980s, in the context of the successive Conservative governments.